QSAR prediction of toxicity for a new 1,2,4-triazole derivatives with 2-bromo-5-methoxyphenyl fragment - Skoryi, M. P.; Shcherbyna, R. O.; Скорий, М. П.; Щербина, Роман Олександрович (Запорізький державний медико-фармацевтичний університет, 2024)
The aim of this study was to evaluate the toxicity of new derivatives of 5-(2-bromo-5-methoxyphenyl)-4-R-1,2,4-triazole-3-thiols, their acids, and esters using the QSAR method to predict parameters of acute toxicity (LD50) and to assess the influence of various radicals on the toxicity of the compounds. Materials and methods. The objects of this study were derivatives of 5-(2-bromo-5-methoxyphenyl)-4-R-1,2,4-triazole-3-thiols, synthesized at the Department of Toxicological and Inorganic Chemistry of Zaporizhzhia State Medical and Pharmaceutical University. The nearest neighbor method was used for toxicity evaluation, applying the Toxicity Estimation Software Tool (TEST). The prediction of rats lethal dose (LD50) was based on the structural similarity of the studied compounds with known substances that have experimental toxicity data. Results. The QSAR analysis revealed that structural modifications in the derivatives of 5-(2-bromo-5-methoxyphenyl)-4-R-1,2,4-triazole- 3-thiols significantly influence their toxicity. Specifically, increasing the size of the radicals, especially through the introduction of aromatic fragments, contributed to the enhanced safety of the compounds, as evidenced by the increase in LD50 values. The highest LD50 values were observed for compounds containing phenyl radicals. Мета роботи – оцінювання токсичності нових похідних 5-(2-бромо-5-метоксифеніл)-4-R-1,2,4-тріазол-3-тіолів, їхніх кислот та естерів за допомогою методу QSAR для прогнозування параметрів гострої токсичності (LD50) і визначення впливу різних радикалів на токсичність сполук. Матеріали і методи. Об’єкти дослідження – похідні 5-(2-бромо-5-метоксифеніл)-4-R-1,2,4-тріазол-3-тіолів, синтез яких здійснили на кафедрі токсикологічної та неорганічної хімії Запорізького державного медико-фармацевтичного університету. Для оцінювання токсичності використано метод найближчих сусідів із застосуванням утиліти Toxicity Estimation Software Tool (TEST). Прогнозування летальної дози (LD50) для щурів ґрунтувалося на структурній схожості досліджених сполук з уже відомими речовинами, що мають експериментальні дані щодо токсичності. Результати. QSAR-аналіз показав, що структурні зміни в похідних 5-(2-бромо-5-метоксифеніл)-4-R-1,2,4-тріазол-3-тіолів суттєво впливають на їхню токсичність. Так, збільшення розміру радикалів, особливо введення ароматичних фрагментів, сприяє посиленню безпечності сполук. Це підтверджено збільшенням значень LD50. Найвищі значення LD50 встановлені для сполук із фенільними радикалами.
QSAR-прогнозування токсичності нових похідних 1,2,4-тріазолу, що містять 2-бромо-5-метоксифенільний фрагмент
Skoryi M. P. - ORCID ID: 0009-0003-7626-1012; Shcherbyna R. O. - ORCID ID: 0000-0002-9742-0284.
Keywords: 1,2,4-triazole; QSAR; toxicity; prediction; 1,2,4-тріазол; токсичність; прогнозування